Analisis Penyusunan Rencana Kebutuhan Barang Milik Daerah dalam Mendukung Tertib Administrasi Aset pada Bidang Aset BPKAD Kota Palangka Raya - Salomo Sinaga; Anike Retawati; MHD Daffa Ashari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the preparation of the Regional Government Property Needs Plan in supporting orderly asset administration at the Asset Division of BPKAD Palangka Raya City. This research uses a qualitative approach with a descriptive method through interviews, observation, and documentation. The results show that the preparation of RKBMD has been carried out through several stages, starting from the submission of needs by OPDs, data input through the RKBMD application, document checking, verification by the Asset Division, to the proposal for official determination. The process has been supported by an application-based system and physical administrative documents. However, several obstacles are still found, such as incomplete supporting data, mismatches between proposed needs and asset records, delays in data input by OPDs, and the need for better technical understanding in coding and classifying goods. This study emphasizes the importance of strengthening coordination, updating inventory data, and improving technical guidance so that RKBMD preparation can support more effective, orderly, and accountable asset administration.